2020
DOI: 10.1177/1120700020978643
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum creatine kinase and C-reactive protein after posterior and direct anterior approaches in total hip arthroplasty

Abstract: Purpose: Some studies reported that measuring serum creatine kinase (CK) level is an objective method with which to determine the relative invasiveness of surgery. The purpose of this study was to evaluate the change in postoperative serum CK levels as a measure of whether the direct anterior approach (DAA) is less invasive than the posterior approach (PA) regarding postoperative rehabilitation. Materials and methods: We prospectively recruited 71 women who were undergoing total hip arthroplasty, 47 were treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Several studies have already shown that the access-related operating time is highly dependent upon the surgeon's experience [59]. Maezawa et al reported a difference in CRP levels between the direct anterior approach (DAA) and posterior approach (PA) on day 1 after the operation, but not on day 4 in a study comprising 71 women [64]. As the number of overall cases in this study is rather small compared to our study and the influence of possible previous diseases is not considered, the reported significant difference on the first postoperative day could be a detection bias.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already shown that the access-related operating time is highly dependent upon the surgeon's experience [59]. Maezawa et al reported a difference in CRP levels between the direct anterior approach (DAA) and posterior approach (PA) on day 1 after the operation, but not on day 4 in a study comprising 71 women [64]. As the number of overall cases in this study is rather small compared to our study and the influence of possible previous diseases is not considered, the reported significant difference on the first postoperative day could be a detection bias.…”
Section: Discussionmentioning
confidence: 99%